Lifestyle Factors are Related to Hypertension in Indonesia: K-Means Clustering And Correlational Study - Syahroni, Arfan; Cahyati, Widya Hary; Budiono, Irwan (Universitas Negeri Semarang, 2025)
Background: Hypertension is a major health problem in Indonesia with complex risk factors, including lifestyle. This study aims to analyze the relationship between consumption of salty foods, instant noodles, sweet drinks, and smoking with the prevalence of hypertension at the provincial level. Methods: This cross-sectional study used data from 38 provinces in Indonesia in 2023. Normality tests were carried out followed by Spearman correlation analysis to measure the relationship between variables. Results: Consumption of salty foods showed a strong positive correlation with hypertension (p<0.001), while instant noodles had a moderate negative correlation that was not significant (p=0.052). No significant relationship was found between hypertension and consumption of soft drinks (p=0.210), energy drinks (p=0.280), or smoking (p=0.540). Conclusion: Excessive salt intake is a dominant risk factor for hypertension in Indonesia, which requires policy intervention, and the insignificance of other lifestyle factors requires further research with a longitudinal approach and multivariate analysis.